Open Ankle Reconstruction of Lateral Ligaments (O-Anti-RoLL). Issue 2 (20th June 2022) - Glazebrook, Mark; Stone, James W.; Pasache Lozano, Rocio del Pilar; Morash, Joel; Takao, Masato
Abstract : Ankle instability is a disabling condition that severely affects people's quality of life. Nonoperative options have been suggested however a surgical procedure is often required to improve symptomatology and function of the ankle joint. In the current paper we describe a surgical technique of an open ankle reconstruction of the lateral ligaments (O-Anti-RoLL), which is a simple and safe surgical technique that utilizes an anatomic Y-graft. Level of Evidence: Diagnostic Level V. Expert opinion. See Instructions for Authors for a complete description of levels of evidence.